Development of blast resistant rice variety through marker-assisted backcrossing between varieties MR263 and Pongsu Seribu 1 - Hasan, Muhammad Mahmudul (2015)
The rice blast caused by Magnaporthe oryzae is the most important and potentially damaging rice disease globally. Its frequent appearance during all stages of plant growth greatly decreases yield and grain quality. Marker-assisted backcrossing (MABC) selection can play a vital role in developing disease resistant, high-yield or quality rice varieties by incorporating a gene of interest into an elite variety that is already cultivated by farmers. The main objective of this study was to develop a blast resistant rice variety from cross between MR263 and Pongsu Seribu 1 (PS1). The specific objectives were to introgress blast resistant genes derived from a resistant variety, PS1 into the popular but blast susceptible Malaysian rice variety MR263 through MABC, to identify polymorphic SSR markers associated with blast resistant genes for foreground selection, to identify polymorphic SSR markers between the two parents, and to evaluate agronomic performance of advanced blast resistant rice lines of BC2F3 generation. A total of 450 SSR markers were used among which 65 polymorphic markers were identified including Pi gene based markers and background markers to identify the segregation ratio in 300 individuals of BC2F1 rice population derived from MR263  PS1. For the phenotypic study, the most virulent blast (Magnaporthe oryzae) pathotype P7.2 was used to screen BC2F1 individuals to determine the inheritance of blast resistance as well as linkage association with the SSR markers. Among the 65 polymorphic markers, 16 markers showed a heterozygous band in the BC2F1 population. From the 16 polymorphic markers, only eight markers (RM5961, RM263,RM163, RM224, RM262, RM168, RM229 and RM169) showed a good fit to the expected segregation genotypic ratio (1:1) for the single dominance gene model (df =1.0, P < 0.05) using chi-square (χ2) analysis. Phenotypic data analysis of the BC2F1 population also showed a good fit to the expected phenotypic ratio (1:1; R:S) for resistant and susceptible plants. Resistance to blast Pathotype P7.2 in PS1 is most likely controlled by a single dominant gene whereby the eight markers are linked to rice blast resistance. These linked-markers could be used in marker-assisted selection programme to develop a durable blast resistant rice variety. From BC2F2 generation,four blast resistant lines (MR263-BR-3-2, MR263-BR-4-3, MR263-BR-13-1 and MR263-BR-26-4) were selected for rice blast resistant varietal development. These lines were identified to carry the Pi-7(t), Pi-d(t)1, and Pir2-3(t) genes and the qLN2 QTL as determined by markers RM5961 and RM263 (linked-marker to the blast resistant genes and QTL). Background selection analysis using 65 polymorphic SSR markers revealed that high recurrent parent genome recovery was 96.0% in MR263- BR-4-3, 94.1% in MR263-BR-3-2, 89.5% in MR263-BR-26-4 and 89.1% in MR263-BR-13-1, and these four resistant BC2F2 lines were selfed to develop BC2F3 population. Finally, thirty advanced blast resistant BC2F3 lines were selected for agromorphological evaluation. Out of 30 blast resistant lines, 12 lines (Lines 12, 6, 7, 5, 21, 22, 26, 11, 8, 10, 13 and 15) produced comparable grain yield per hill, number of tillers per hill, panicles per hill and percentage of filled grain to variety MR263. The estimates broad-sense heritability values in the selected rice population were high (70 to 95%) for all the traits indicating that these characteristics are highly heritable to the next generation. From cluster analysis based on the agro-morphological traits, 20 advanced lines were grouped into similar cluster with MR263 variety. This result was expected due to a high genome recovery (mean 96%) of MR263 variety into the advanced lines. The 12 advanced rice lines are recommended for multi-location trial to select blast resistant high yielding lines for development of highly potential rice variety in Malaysia.